Prevalence of low Vitamin D Levels in Patients with Irritable Bowel Syndrome at a Tertiary Care Hospital of Nepal - Agrahari, Mahendra; Singh, Ranjita; Sapkota, Kalyan; Gautam, Mani Prasad (Journal of Bharatpur Hospital, 2025)
Background Vitamin D deficiency is a common disorder prevalent among both developed and developing countries. Irritable Bowel Syndrome has been linked to many diseases and conditions. Very few studies of vitamin D deficiency status have been done in Nepalese population. This study aims to find out the prevalence of low levels of Vitamin D in patients with Irritable Bowel Syndrome attending the outpatient department of a tertiary center. Methods This descriptive cross-sectional study was conducted in patients with Irritable Bowel Syndrome attending the outpatient department of Bharatpur Hospital, Chitwan, Nepal between 15, June 2024 to 20, august 2024. Ethical approval was taken from Bharatpur Hospital (Ref: 081/82-045). Sample size is 71. Data collection tools for self-administered questionnaire, the collected data was entered and analyzed in Microsoft Excel. Point estimate at 95% confidence interval was calculated along with frequency and proportion for binary data. Results Out of a total of 71 patients with Irritable Bowel Syndrome, the prevalence of low levels of vitamin D insufficiency was seen in 36 (50.7%) and deficiency was seen in 35 (49.3%). Clinical features were studied in the vitamin D deficient and vitamin D insufficient patients which included weakness, altered bowel habits, pain abdomen and lower back pain. Levels of vitamin D in IBS, the study of the stool frequencies showed most common to be once in more than 2 days numbered as 17 (24.0%). Conclusions Based on the findings of the study it concludes that low Vitamin D levels among patients with Irritable Bowel Syndrome. Vitamin D deficient and vitamin D insufficient patients which included weakness, altered bowel habits, pain abdomen and lower back pain.